2006
DOI: 10.3998/ark.5550190.0007.903
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent iodine(V) reagents in organic synthesis

Abstract: This review summarizes the synthetic applications of hypervalent iodine(V) reagents: iodylbenzene, IBX (2-iodoxybenzoic acid), DMP (Dess-Martin periodinane) and pseudocyclic IBX analogs. Application of these reagents allows mild and highly selective oxidative transformations in a facile and environmentally friendly manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…Their easy availability, high stability, controlled oxidizing ability, and environmentally benign nature make them highly suitable for the development of new synthetic transformations [1317]. The chemistry of iodine(V) reagents has been well documented in a number of reviews [1820]. In continuation of our research focus on the development of synthetic methods using iodine-based reagents [2126], we here report a method for the synthesis of quinazolin-4(3 H )-ones [2728] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Their easy availability, high stability, controlled oxidizing ability, and environmentally benign nature make them highly suitable for the development of new synthetic transformations [1317]. The chemistry of iodine(V) reagents has been well documented in a number of reviews [1820]. In continuation of our research focus on the development of synthetic methods using iodine-based reagents [2126], we here report a method for the synthesis of quinazolin-4(3 H )-ones [2728] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A focused literature survey on the use of IBX in the oxidation of alcohols under anhydrous conditions revealed that there were reports on the use of IBX -BTPP combination in the oxidation of alcohols. [38][39][40][41][42][43][44][45] Based upon these studies it was planned to explore this reagent-oxidant combination in the oxidation of 1a. Accordingly, a model reaction was carried wherein a mixture of 1a (1mmol), IBX (0.1 mmol) and BTPP (1 mmol) in dry acetonitrile (5 mL) was stirred under reflux conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Although IBAs can be prepared from 2-IBs by existing methods ( Figure 2 ) [ 63 , 64 , 65 , 66 ], the development of a safer and more efficient method for their synthesis is highly desirable. As shown in Figure 2 , IBAs can be further oxidized to pentavalent cyclic hypervalent IBXs [ 67 ], which need to be prevented for the preparation of IBAs [ 68 , 69 , 70 ], mainly due to the explosive nature of IBXs on heating and impact, while IBXs are useful in some small-scale reactions [ 71 , 72 , 73 , 74 , 75 , 76 ]. Thus, contamination by IBX in the IBA products should be avoided for long-term safe storage or large-scale use.…”
Section: Introductionmentioning
confidence: 99%